Breeding biology of the spineless cuttlefish Sepiella inermis (Orbigny) - Neethiselvan, N; Venkataramani, V K; Ramanathan, N (Indian Journal of Fisheries, 2011)
Studies on the seasonal occurrence of maturity stages of Sepiella inermis revealedthat this species is a prolonged breeder as mature and spent specimenswere recorded almost round the year. Two peak spawning periods, one in Novemberand another in March were observed. Mature animals were representedby a wider length range ruling out the possibility of semelparity. Thegonodosomatic and nidamental gland indices increased during maturation. Thefemales attained maturity earlier than males. Fecundity showed a significantcorrelation with dorsal mantle length. Cuttlefishes contribute substantially tothe cephalopod fishery of Thoothukkudi (8°47’ N,, 78°9’ E), located in south eastcoast of India. Out of the three species of cuttlefishes, viz. Sepia pharaonis,Sepia aculeata and Sepiella inermis, which form commercial fishery in this coast,S.inermis is notable for its year round occurrence.